Laser-Assisted Production of Carbon-Encapsulated Pt-Co Alloy Nanoparticles for Preferential Oxidation of Carbon Monoxide - Martinez, Gema; Malumbres, Ana; Lopez, Angela; Mallada, Reyes; Hueso, Jose L.; Santamaria, Jesus (Frontiers in Chemistry, 2018)
C-encapsulated highly pure PtxCoy alloy nanoparticles have been synthesized by an innovative one-step in-situ laser pyrolysis. The obtained X-ray diffraction pattern and transmission electron microscopy images correspond to PtxCoy alloy nanoparticles with average diameters of 2.4 nm and well-established crystalline structure. The synthesized PtxCoy/C catalyst containing 1.5 wt % of PtxCoy nanoparticles can achieve complete CO conversion in the temperature range 125-175 ºC working at weight hourly space velocities (WHSV) of 30 L h-1g-1. This study shows the first example of bimetallic nanoalloys synthesized by laser pyrolysis and paves the way for a wide variety of potential applications since there are many possible metals combinations.